Modern biomarkers of acute kidney injury - D. I. Korabelnikov; M. O. Magomedaliev (Фармакоэкономика)
The results of published studies of modern biomarkers used in the diagnosis of acute kidney injury (AKI) were summarized. The search was carried out in the PubMed/MEDLINE, Scopus, eLibrary databases. AKI occurs in 10–15% of all inpatients and 50% of intensive care patients, and affects economic aspects of treatment and rehabilitation. The literature review allowed to draw conclusions about the significant advantage of new AKI biomarkers (cystatin C, neutrophil gelatinase-associated lipocalin, β2-microglobulin, kidney injury molecule-1, fatty acid binding protein) over the conventional glomerular filtration rate, serum creatinine and urinary volume. Serum creatinine increases only in cases when 50–60% of nephrons are damaged, urinary volume has limitations such as the overdiagnosis of AKI in dehydrated patients, the inability to assess based on a single measurement, and the need for regular and frequent follow-up. Modern biomarkers make it possible to verify renal dysfunction in advance, at the subclinical level. This allows to make a correction in the therapy of the underlying disease and initiate nephroprotection to prevent the development of AKI and the further development of multiple organ failure, which may be more effective than the treatment of already developed AKI.